RELASI AGAMA DAN NEGARA (STUDI KOMPARASI PEMIKIRAN NURCHOLIS MADJID DAN ABDURRAHMAN WAHID): Religion and State Relations (Comparative Study of the Thoughts of Nurcholis Madjid and Abdurrahman Wahid) - Rafid Abbas; Muhammad Danial (UIN Kiai Haji Achmad Siddiq Jember, 2022)
Religion and the State are two important things that cannot be separated from human life. This study raises the thoughts of Nurcholis Madjid and Abdurrahman Wahid regarding the relationship between religion and the state, namely a state based on the values of Pancasila. Pancasila has been widely discussed by Muslims from both secular and nationalist schools. Although Islam is not shown in Pancasila, Islamic values still exist and are positioned as neutral as possible, while according to Abdurrahman Wahid, religion plays a role as a source of the nation's and state's view of life. The purpose of the research is to find out and compare (comparison) the thoughts of Nurcholis Madjid and Abdurrahman Wahid regarding the relationship between religion and the state. The type of research is library research which focuses and limits activities in the library to obtain data. The results of the study state that the thoughts of Nurcholis Madjid and Abdurrahman Wahid regarding the relationship between religion and the state are the most suitable for Indonesia, namely the Pancasila state, which is a country based on the values of Pancasila. Then the comparison (comparison) of the thoughts of Nurcholis Madjid and Abdurrahman Wahid regarding the relationship between religion and the state is that religion and the state must complement and strengthen each other, so the middle way that is suitable for this is Pancasila. Agama dan Negara merupakan dua hal penting yang mustahil dipisahkan dari kehidupan manusia. Penelitian ini mengangkat Pemikiran Nurcholis Madjid Dan Abdurrahman Wahid Mengenai Relasi Agama Dan Negara, yakni Negara yang berlandaskan nilai-nilai Pancasila. Pancasila sudah banyak dibahas oleh kaum muslim baik dari aliran sekuler maupun nasionalis. Meskipun Islam tidak ditampakkan dalam Pancasila, namun nilai Islam masih ada dan diposisikan senetral mungkin, sedangkan menurut Abdurrahman Wahid, agama berperan menjadi sumber pandangan hidup bangsa dan Negara. Tujuan penelitian untuk Mengetahui dan membandingkan (Komparasi) Pemikiran Nurcholis Madjid Dan Abdurrahman Wahid Mengenai Relasi Agama Dan Negara Jenis penelitian adalah kepustakaan (library research) yang memusatkan dan membatasi kegiatan pada perpustakaan untuk memperoleh dataHasil penelitian menyatakan bahwa Pemikiran Nurcholis Madjid Dan Abdurrahman Wahid Mengenai Relasi Agama Dan Negara yang paling cocok untuk Indonesia adalah negara Pancasila yakni negara yang berlandaskan nilai-nilai Pancasila. kemudian perbandingan (Komparasi) Pemikiran Nurcholis Madjid Dan Abdurrahman Wahid Mengenai Relasi Agama Dan Negara adalah antara agama dan negara harus saling mengisi dan menguatkan satu sama lainnya, maka jalan tengah yang cocok untuk hal demikian adalah Pancasila.